Unusual course of AA amiloidosis in a patient with rheumatoid arthritis - Y V Muravjev; S G Radenska-Lopovok; A V Alexeeva; E G Lyubimova; T M Novoselova (Научно-практическая ревматология, 2009)
A case of an unusual course of AA-amyloidosis in a pt with rheumatoid arthritis – disseminated amyloid deposition in lungs, heart and liver with insignificant and variable proteinuria – is presented